2022
DOI: 10.1186/s12884-022-04492-7
|View full text |Cite
|
Sign up to set email alerts
|

Does the cell number of 0PN embryos on day 3 affect pregnancy and neonatal outcomes following single blastocyst transfer?

Abstract: Background 0PN zygotes have a low cleavage rate, and the clinical outcomes of cleavage-stage embryo transfers are unsatisfactory. Blastocyst culturing is used to screen 0PN embryos, but whether the cell number of 0PN embryos on day 3 affects the clinical outcomes following single blastocyst transfer is unknown and would be helpful in evaluating the clinical value of these embryos. Methods This retrospective study compared 46,804 0PN zygotes, 242 0P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…In this study, D5 good blastocyst formation rate was higher in 0PN embryos and most of the transferred blastocysts ( 80%) were D5 blastocysts and good-quality blastocysts, which may be the reason for no signi cant differences in CPR and LBR between the 0PN and 2PN blastocyst transfers before and after matching. And recent studies also supported our results [9,34,42,43]. For neonatal outcomes, 0PN-VBT was associated with increased birthweight and a higher risk for very LGA newborns was reported by Li et al, [42], which was not observed in the study.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, D5 good blastocyst formation rate was higher in 0PN embryos and most of the transferred blastocysts ( 80%) were D5 blastocysts and good-quality blastocysts, which may be the reason for no signi cant differences in CPR and LBR between the 0PN and 2PN blastocyst transfers before and after matching. And recent studies also supported our results [9,34,42,43]. For neonatal outcomes, 0PN-VBT was associated with increased birthweight and a higher risk for very LGA newborns was reported by Li et al, [42], which was not observed in the study.…”
Section: Discussionsupporting
confidence: 90%
“…Blastocyst culture is commonly recommended to select development potential for 0PN embryos [22]. Chen et al reported that the available blastocyst rates of 0PN embryos were decreased when compared with those of 2PN embryos, and the cell number of 0PN embryos on day 3 affected subsequent blastocyst formation [23]. The available blastocyst rate of 0PN embryos was higher for the ≥6 cells than <6 cells day 3 embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported a decrease in the available blastocyst rates of 0PN embryos compared with those of 2PN embryos, and the cell number of 0PN embryos on day 3 affected subsequent blastocyst formation [ 21 ]. The available blastocyst rate of 0PN embryos was higher for ≥ 6-cell than < 6-cell day 3 embryos.…”
Section: Discussionmentioning
confidence: 99%